JANJI POLITIK DALAM AL-QUR’AN (Study Komparatif Tafsir Ibnu Katsir Al-Qur’an Al-adzim dan Sayyid Qutb Fi Dzilalil Qur’an) - Rizki Kurniawan; Miftarah Ainul Mufid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to provide understanding and advice to politicians to always be ethical in politics, especially in making promises when seeking votes, even though it cannot be denied that politics is a sensitive activity, for this reason the author provides an understanding through the guidelines of Muslims (the Qur'an), so as not to go astray from the direction of sharia in politics.This research is basically a library research, namely research conducted by collecting data or scientific papers that are relevant to the object being studied. Before conducting a review of the library materials, researchers must first know for sure about the sources from which the scientific information was obtained. Many image-building practices occur during democratic elections to garner public votes and increase popularity for personal gain. Therefore, the author will focus on examining political verses in the Quran used as campaign promises by politicians or prospective leaders. Taking some political verses which were then interpreted by the book of Ibn Kathir's commentary on the Qur'an al-adzim and the book Fi Dzilalil Qur'an by Sayyid Qutb, using the muqorrin or comparative method. Here we will compare some of these verses and compare their interpretations, assessing from two different points of view of the interpreters, looking for similarities and differences between the two interpreters. Then the author's research results are implied in contemporary life today, concluding how a politician's attitude in politics and making promises should remain in accordance with the sharia and the guidelines of the Qur'an, from a comparison of the two commentators and analyzing the advantages and disadvantages of the interpretations of Ibn Kathir and Sayyid Qutb.